(3GdChQGb GdJLGQjI GdeYGUQIs - (3eMeO Hf HdYjO Cefh(B, (3GdHhWjHjs ((3HjQhJ(B:s (3OGQ GdcJH GdYdejI(B,s, 2006)
(3jVe eaghe GdJLGQI heTQhYjJgG aj GdESdGe, GdVhGHW GdTQYjI aj eLGd GdeYGedGJ GdJLGQjI, JYQja GdChQGb GdJLGQjI , NUGFU GdChQGb GdJLGQjI , CfhGY GdChQGb GdJLGQjI , fTCI GdChQGb GdJLGQjI , GdaQb Hjf GdChQGb GdJLGQjI hGdeGdjIs
(3GdeQGLY U(B.373s
Keywords: (3GdChQGb GdJLGQjIs; (3GdEbJUGO GdESdGejs; (3GdJLGQIs